Bait Duabelas: Studi Naskah Suluk Kiai Kemuning Panti Jember: Bait Duabelas: A Study of the Suluk Manuscript of Kiai Kemuning from Panti, Jember - Muhammad Ardiansyah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
The coming of Islam in Indonesia touched the existing local traditions. In Java especially, Islam introduced a concept of local wisdom as rahmatan lil alamin. However, some people viewed this as a deviation from the purity of Islam. Bait Duabelas (Twelve Stanzas) represents the